Pengaruh Motivasi, Kompensasi, Kompetensi Dan Beban Kerja Terhadap Kinerja Kerja Karyawan Pada PT. Sapadia Wisata rantauprapat - Pangestu, Ridho (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of motivation, compensation, competence and workload on employee performance at PT. Sapadia Tourism Rantauprapat. This Type Of Research Is Associative Research. Data collection in this study was conducted through a survey approach with the type of quantitative descriptive research by distributing questionnaires to 30 respondents, while the population used in this study are employees at PT. Sapadia Tourism Rantauprapat. Data collection techniques were carried out by interviews, questionnaires and documentation studies. Data analysis tools used in this study using SPSS (Statistical Product Software Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and coefficient of determination test (R2). The results of this study showed that partially motivation positive and significant effect on the performance of employees at PT. Sapadia Wisata Rantauprapat with thitung value (3.319) > ttable 1.710) and significance level 0.003 < 0.05. Partial compensation has a positive and significant effect on employee performance at PT. Sapadia Wisata Rantauprapat with thitung value (4.208) > ttable (1.710) and significance level 0.000< 0.05. Partially competence positive and significant effect on employee performance at PT. Sapadia Wisata Rantauprapat with thitung value (3.716) > ttable (1.710) and significance level 0.001< 0.05. Then partially workload positive and significant effect on employee performance at PT. Sapadia Wisata Rantauprapat with thitung value (5.874) > ttable (1.710) and significance level 0.000< 0.05. In simultaneous testing (test F) known that simultaneously motivation, compensation, competence and workload positive and significant effect on employee performance at PT. Sapadia Wisata Rantauprapat with the results showed that the value of the calculation is (14.083) > Ftable (2.76) and the significance level of 0.00 < 0.05. Through testing the coefficient of determination (AdjustedR Square) of 0.643. This value means that work performance can be explained by motivation, compensation, competence and workload of 64.3%. While the remaining 35.7% influenced by other variables that are not examined in this study.